Social Interaction and Religious Tolerance in Malay Community of Jambi - Kailani, Mohd; Halim, Abdul; Mustaniruddin, Ahmad; Mubarak, Zaki; Kusnadi, Edy (Farabi, 2024)
This research analyzes the patterns of social interaction and tolerance between the Malay community and the Batak ethnic group in Bagan Pete, Jambi City. Known for its pluralistic characteristics since the pre-independence era, Jambi City shows how ethnic diversity can be a positive force instead of a source of conflict. Jambi City's Bagan Pete became the focus of the research due to its high diversity driven by the presence of Jalan Lintas Timur and Alam Barajo Terminal, which attracted many migrants, especially ethnic Batak who are predominantly Christian. Through a qualitative approach with in-depth interviews with ten key informants, the research reveals the complex social dynamics between the two communities. The results show that social interactions manifest in various forms, including cooperation, conflict, competition and accommodation. Positive interactions are mainly seen in daily social and economic activities, with conflicts that arise generally minor in nature and can be resolved through constructive dialogue. Religious tolerance is a prominent aspect, shown through the Malay community's respect for different beliefs, reinforced by initiatives to develop religious understanding through study groups, Islamic schools, and Qur'anic learning. The findings have practical implications for local government policy development and community development, including the importance of interethnic interaction programs, interfaith dialogue, and strengthening the role of community leaders in maintaining social harmony.